Reimagining De-urbanised Madrasa and Self-place Interaction Through the Lens of Psychogeography - Mohd Muzhafar Idrus; Normazla Ahmad Mahir; Norhaili Massari; Habibah Ismail (Springer Nature, 2025)
Indexed by WOS